The Effectiveness of the Kazdin Method for Parenting on Parent-Child Relationships among the Students with Oppositional Defiant Disorder - Maryam Fooladvand; Mohammad Ali Nadi; Ahmad Abedi; Ilnaz Sajjadian (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2018)
Aim and Background: Oppositional Defiant Disorder (ODD) is a gradual and chronic one always interacting with Cook’s interpersonal relationships and academic performance. Parenting is one of the effective methods for ODD, in which parents learn how to treat their children. The present study aimed to investigate the effectiveness of the Kazdin method for parenting on parent-child relationships among the students with ODD.